Proyecto de sistemas de citas de la empresa toyocosta s.a. - Navarro Quiroz, Rosa (2009)
The company Toyocosta S.A. constituted the 8 of August of the year 2000 and was approved by the Supervision of companies the 11 of September of the same year; the founders were: Guillermo Vázquez Astudillo and Fabian Baca Cobo . Toyocosta S.A. has 4 lines of business that are: VEHICLES, SPARE PARTS, FACTORIES AND RENT. Intention of the Company “We offer STATUS AND SATISFACTION through a solution of permanent transport, with opportune service, competitive and guaranteed, in order to fortify the image of the company, to obtain the development of the human potential with property sense and a right remuneration, to obtain a suitable yield for our shareholders, fulfilling our social responsibility, basing us on the TMC philosophy” Toyota Motor Corporation presented its concessionaires the Procedure on watch 7 steps, that helped to fulfill the TSM Kodawari, these steps assure efficient operations on watch that they generate lucrative quality in the service to the client and businesses, is born the necessity here from the implementation from the System from Appointments for the factory. Citas is the first step that is used to take care of the clients of the factory efficiently. On the basis of this and to the continuous improvement the concessionaire would describe for the TOYOTA.